Capitales de las comunidades las Brisas, Camarón Chorrillo, San Luís y su incidencia en los medios de vida - Rivas Domínguez, Ruddy Lisbeth (2017)
This study was aimed to characterize the seven capitals in the Carrizal sub-basin and analyze the relationship that exists with the life strategies used, the methodology for the analysis of the variables and indicators was based on the capital approach of the communities, where the same degree of emphasis to each of the indicators for "prosperity generation " is given, with great ecological importance in the conservation of natural capital, as key elements for conceiving direct and indirect welfare to human communities. The livelihoods study is a tool to characterize the complex combination of different production and income-generating activities for the welfare of poor communities. Thus, it presents a key way of conceiving the objectives, scope and priorities of capitals. The methodology used led to the application of a Rapid Rural Diagnosis (RRD), obtaining the current situation of economic activities in the families, followed by a survey to know the capitals and livelihoods, grouping the families by homogeneous groups. By obtaining synthetic indexes of the different practical capitals used by the families, the correlation of the capitals generated very similar results; therefore, the site Las Brisas was characterized by greater accessibility in natural and human capital, Camarón Chorrillo and San Luis mostly have physical, natural and cultural assets. Livelihoods are concentrated mainly in agriculture, livestock farming, minor animal husbandry, and work on farms in advance.